The Process of Xylanase Production from Bacillus pumilus RXAIII-5 - NUR RICHANA; TUN TEDJA IRAWADI; M. ANWAR NUR; ILLAH SAILAH; KHASWAR SYAMSU (Microbiology Indonesia, 2007)
The optimum conditions for the growth of Bacillus pumilus RXAIII-5 (a potential xylanase producer) were sought, these included temperature, pH, aeration, and agitation of the culture batch. Afterwards a mathematical model based on the parameter of cultivation kinetics was formulated. At the same time, the rheology of the fluid used for bacterial cultivation in a bioreactor was studied. The data obtained was used for estimating the ‘scaling up’ of enzyme production. The results of the study indicate that the optimum condition for processing in 50 ml Erlenmeyer flask are used temperature of 35 oC (308oK), pH 7, and an agitation rate of 140 rpm. The highest xylanase activity and its specific activity are 297.132 U.ml-1 and 655.32 U.g-1protein, respectively. Subsequent experiments in a bioreactor using all of the experiment parameters mentioned above, except for the agitation rate, shows that the results are as follows. The highest specific growth was at 0.082 hour-1 at an aeration and agitation rate of 0.5 vvm and 150 rpm, respectively. Based on the data of the cultivation kinetics, the optimum conditions for the fermentation in Biostat 2L-bioreactor is 1 vvm and 200 rpm of aeration and agitation, respectively . The efficiency of substrate (Yp/s) and of cell biomass (Yp/x) to produce xylanase is 50.744 U.g-1 and 43.906 U.g-1, respectively. The efficiency of substrate to cell production (Yx/s) is 1.178g.g-1. The liquid cultivation-medium has non-Newtonian properties. Based on a mathematical model it is found that the consistency index (k constant) and index of liquid behavior (n value) are 0.179 g.cm-1.second-1 and 0.3212, respectively. Becouse the value of 0